2000
DOI: 10.1093/ajcn/72.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical effects of a diet containing foods enriched with n−3 fatty acids

Abstract: Foods that are strategically or naturally enriched in n-3 fatty acids can be used to achieve desired biochemical effects without the ingestion of supplements or a change in dietary habits. A wide range of n-3-enriched foods could be developed to support large-scale programs on the basis of the therapeutic and disease-preventive effects of n-3 fatty acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
2
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(118 citation statements)
references
References 16 publications
8
100
2
8
Order By: Relevance
“…Some studies, that supplemented daily doses of 14-18 g of ALA a day, showed effects on endothelial function, but others that supplemented lower doses did not (Sanderson et al, 2002). Both EPA and ALA have been shown to decrease the synthesis of cytokines (Mantzioris et al, 2000;De Caterina & Basta, 2001). Rallidis et al (2003) found, in a population similar to ours, a lower level of CRP with a 3-month increased intake of ALA.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Some studies, that supplemented daily doses of 14-18 g of ALA a day, showed effects on endothelial function, but others that supplemented lower doses did not (Sanderson et al, 2002). Both EPA and ALA have been shown to decrease the synthesis of cytokines (Mantzioris et al, 2000;De Caterina & Basta, 2001). Rallidis et al (2003) found, in a population similar to ours, a lower level of CRP with a 3-month increased intake of ALA.…”
Section: Discussionsupporting
confidence: 78%
“…Potential mechanisms of action include a decreased response of platelets to aggregation (Freese et al, 1994), a lower concentration of serum triacylglycerol (Schmidt et al, 1993), and a decreased vascular smooth muscle cell proliferation (Pakala et al, 1999). Furthermore, n-3 fatty acids may have anti-inflammatory effects, possibly by affecting cytokine synthesis (Endres, 1996;Mantzioris et al, 2000;De Caterina & Basta, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Lovegrove et al (1997) fortified some everyday items with fish oil such as bread and spread, along with a number of sweet foods, including biscuits, cake, ice cream, and milkshake powder, and used a portion exchange system with the aim of achieving a daily intake of 1.8 g EPA þ DHA. Likewise, Mantzioris et al (2000) used a similar dietary approach with fish-oil-fortified savoury products like sausages and dip, and had a large emphasis on ingestion of fresh fish, and set a target EPA content in mononuclear cell phospholipids of 1.5% of total fatty acids. Subjects achieved mean daily intakes of EPA þ DHA of 1.4 and 1.8 g, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have used similar foods to those used by Mantzioris et al (2000) with the addition of fish-oilfortified margarine spread and long-life milk. This is the first study to examine the food preferences of the subjects, and the contribution of the individual food items to the overall intakes of EPA and DHA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation